Peluang Ekspor Maggot Sebagai Biokonversi - Dlorif Rifqi Almusyaffa; Olivia Marentina Sinaga; Muhammad Ramadhani Syah Putra; Rinandita Wikansari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Organic waste management has become an urgent global issue, as the increasing volume of waste poses serious challenges to the environment. One innovative solution that is gaining increasing attention is Maggot cultivation, through a bioconversion process. Maggot bioconversion not only addresses the problem of organic waste but also offers new economic opportunities through the production of high-value resources. In addition, maggot cultivation can also contribute to addressing the high price of protein sources and the increasing demand for animal feed. As highlighted by a study, maggot bioconversion technology can address three main problems: the generation of organic waste, the high price of protein sources, and the increasing demand for animal feed. (Handayani et al., 2021). Maggot (Hermetia Illucens) is a black soldier fly larva that has a chewy texture, high protein and has the ability to secrete natural enzymes that help improve the digestive system of livestock.